The Influence E-Learning Platforms of Undergraduate Education in Iraq - Haider TH. Salim ALRikabi (International Association of Online Engineering (IAOE), 2021)
continue learning. Technology has become not only an activity but also a fundamental tool. Moreover, technology becomes the core media that allows education to happen. In Iraq Blended Learning used to overcome the pandemic and counting education Therefore, the use of computers and digital applications became part of daily life and for long hours. Therefore, properly designed digital educational activities linked to social media have become a powerful educational tool aimed at finding ways of effective learning. The use of interactive activities contributed to the growth of self-learning motivation and the building of a healthy mind capable of finding a way out for the advancement of educational reality when crises occurred. It has become impossible to do without mobile devices, because of the attractive features they have and the multiple advantages they provide in teaching mathematical, medical, and engineering sciences in universities of our study relied on comparing the most important educational platforms with the best operation for managing virtual classes and the auxiliary tools they contain, including adding materials, assignments, tests, and electronic attendance records with archiving classes and migrating students to the advanced stages, as it relied on the electronic administration mechanism. All of these procedures take place through the availability of the Internet.